2021
DOI: 10.14218/jcth.2020.00127
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Model of Ursodeoxycholic Acid Treatment Response in Primary Biliary Cholangitis

Abstract: Background and Aims: Although ursodeoxycholic acid (UDCA) treatment in primary biliary cholangitis is effective in many patients, there are still many people who respond poorly to it. Identifying and intervening these patients early is important. Therefore, exploring the risk factors and proposing a predictor index to predict the UDCA treatment nonresponse earlier among primary biliary cholangitis patients were the aims of this research. Methods: A total of 135 primary biliary cholangitis patients treated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The AUROC of the score model in the derivation group and the verification group was 0.763 (95% CI, 0.701–0.817, P < 0.001) and 0.798 (95% CI, 0.681–0.887, P < 0.001), respectively [31]. A different approach was used in a Chinese study, which elaborated a nomogram to predict the probability of inadequate biochemical response to UDCA, including sex, albumin, and bilirubin levels as influencing factors of drug response [32]. Finally, noninvasive liver fibrosis evaluation using vibration-controlled transient elastography in treatment-naive patients has been suggested for early risk stratification in PBC [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…The AUROC of the score model in the derivation group and the verification group was 0.763 (95% CI, 0.701–0.817, P < 0.001) and 0.798 (95% CI, 0.681–0.887, P < 0.001), respectively [31]. A different approach was used in a Chinese study, which elaborated a nomogram to predict the probability of inadequate biochemical response to UDCA, including sex, albumin, and bilirubin levels as influencing factors of drug response [32]. Finally, noninvasive liver fibrosis evaluation using vibration-controlled transient elastography in treatment-naive patients has been suggested for early risk stratification in PBC [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Prospective studies have reported response rates to UDCA/CDCA treatment ranging from 43.2 to 47.2%. However, with the exception of GB stone size, the factors affecting response to treatment remain unidentified 6 , 7 , 11 13 . Furthermore, no biomarker has been identified that accurately predicts response to UDCA/CDCA treatment for managing GB stones.…”
Section: Introductionmentioning
confidence: 99%